TEACHING, TECHNOLOGY, AND TRANSFORMATION: EXPLORING TEACHER IDENTITY THROUGH DISCOURSE AND DEVELOPMENT NARRATIVES IN NEPAL - Bhandari, Laxman Prasad; Bhandari, Bhim Lal; Baguinat, Naomie S.; Tiwari, Eeba Raj (ppjbsip, 2026)
This study explores secondary English teachers’ engagement in professional development (TPD) initiatives in semi-urban Nepal through a narrative and discourse lens. It investigates how teachers construct professional meaning and identity via their experiences with workshops, technology, peer learning, and classroom action research. Employing a qualitative narrative inquiry design, data were collected through semi-structured interviews and a focus group discussion with four purposively selected English teachers from public secondary schools in Butwal Sub-Metropolitan City, Nepal. Thematic analysis revealed five core areas shaping teacher development: workshops and formal training, collaborative learning, technology and AI integration, classroom teaching strategies, and personal academic activities such as reading and research. Teachers valued collaborative peer practices and technology use as transformative, while highlighting the limitations of top-down PD models and the lack of institutional follow-up. The discourse embedded in their narratives illustrates how they negotiate professional roles, pedagogical authority, and technological agency. The study emphasizes the importance of framing teacher development not only as training but as a dialogic and situated discourse shaped by institutional, technological, and socio-cultural dynamics. It recommends that policy initiatives integrate teacher narratives as discursive evidence to design more effective and inclusive PD models. The study contributes to understanding grassroots teacher development in resource-limited settings and how discourse and narrative shape professional identity. It also holds implications for teacher education programs and researchers interested in educational discourse and professional identity construction